PENDIDIKAN SENI BUDAYA: MENDORONG KREATIVITAS DAN APRESIASI BUDAYA DALAM PEMBELAJARAN - Woro Wurtiningsih (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
Cultural Arts Education has an important role in developing creativity and cultural appreciation in students. This journal discusses the importance of cultural arts education in the context of modern education. We explore strategies and approaches that are effective in integrating arts and culture into the curriculum, as well as their impact on student development. In this journal, we also discuss some of the challenges faced by arts and culture education and provide recommendations to overcome these problems. Through an in-depth understanding of the importance of arts and culture education, it is hoped that we can create a learning environment that enriches and motivates students.